EVALUATION OF MODIFIED KENT-EISENBERG MODEL TO PREDICT HYDROGEN SULPHIDE SOLUBILITY IN METHYLDIETHANOLAMINE - NELSON , YANG SOON KIT (IRC, 2016)
In the designing stage for the unit operation of gas sweetening, the models to determine acid gases solubility are limited and highly complex. Therefore, the aim of this study is to analyse the reliability of a simpler model, the Modified Kent-Eisenberg (KE) Model to predict the solubility of hydrogen sulphide in methyldiethanolamine (MDEA) solution. In this work, Modified Kent-Eisenberg model is re-derived for a different ternary system. The system involved in this research work is a ternary system of H2S-MDEA-H2O system; hence, a different set of ionic dissociation equations of the species involved are used for the derivation of equations to further modify the KE model prior to its evaluation.